Springer handbook of marine biotechnology - Kim, Se-Kwon (Springer Berlin Heidelberg Imprint: Springer, 2015)
The Springer Handbook of Marine Biotechnology provides, for the first time, a complete and consistent overview of the methods, applications, and products of marine biotechnology. Since a large portion of the surface of the earth is covered by the oceans and more than 80% of living organisms are found in aquatic ecosystems, they constitute a rich reservoir for various chemical materials and (bio-)chemical processes. Marine biotechnology studies these biochemical materials and processes from marine sources and makes them available to applications as pharmaceuticals, cosmeceuticals or nutraceuticals as well as for the production of bioenergy and biofuels. Edited by Prof. Dr. Se-Kwon Kim, a renowned expert with a longstanding experience, and including over 60 chapters from leading international scientists, this handbook is a major authoritative desk reference for everyone interested or working in the field of marine biotechnology and bioprocessing. The handbook is divided into 10 parts. Part A: Marine Flora and Fauna. Part B: Tools and Methods in Marine Biotechnology. Part C: Marine Genomics. Part D: Marine Algal Biotechnology. Part E: Marine Microbiology and Biotechnology. Part F: Marine-Derived Metabolites. Part G: Application of Marine Biotechnology. Part H: Bioenergy and Biofuels. Part I: Biomedical Applications. Part J: Industrial Applications. Key topics include: - Marine flora and fauna - Tools and methods in marine biotechnology - Marine genomics - Marine microbiology - Bioenergy and biofuels - Marine bioproducts for industrial applications - Marine bioproducts for medical and pharmaceutical applications - and many more...